Beyond alternation: The primacy of insertion in Qania Fanani’s YouTube code mixing in social media discourse - Saiful Akmal; Nisrin; Asma (Universitas Islam Negeri Ar-Raniry, 2026)
This study investigates the linguistic phenomenon of code-mixing as exemplified in the YouTube content of Qania Fanani, with particular focus on its typological manifestations and the socio-communicative factors that motivate its use. The theoretical framework adopted is drawn from Muysken’s (2013) taxonomy, which delineates code-mixing into distinct structural categories. Employing a qualitative research design grounded in textual analysis, this study examines transcribed data extracted from four selected vlogs. The analysis reveals that insertion constitutes the predominant code-mixing type, occurring 250 times, whereas alternation appears with markedly lower frequency, at 29 instances. These distributional patterns suggest that Qania Fanani’s linguistic practice is characterized by a strategic and naturalistic deployment of code-mixing to achieve communicative functions such as enhanced clarity, discursive emphasis, and stylistic variation. Furthermore, the study identifies key social factors underpinning these patterns, most notably the speaker’s multilingual competence and the presence of lexical gaps, which together point to a high degree of metalinguistic awareness and flexible bilingual proficiency. The findings underscore the organic integration of code-mixing as a discursive resource among digital content creators, facilitating audience engagement and navigation across linguistically diverse communicative contexts. In doing so, this research contributes to the broader understanding of social media as a site of dynamic and situated language practice. Future research is encouraged to examine the receptivity of such code-mixed practices among viewers, particularly regarding potential influences on language preference, comprehension, and the pedagogical implications for language learning within digitally mediated environments.